The Influence Of Sports Activities On The Healthy Lifestyle Of Mothers In SSB Karawang District - Ninda Sugi Nur Diyanti; Salvina Aulia Oktavaiza; Faisal Fasya Al Ghiffari; M. Arief Setiawan (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2024)
This study aims to assess the effect of sports activities on the healthy lifestyle of mothers in SSB Karawang Regency. The study used an experimental method with a pretest-posttest group design. The research sample amounted to 15 people selected using purposive sampling. Data were collected through pre-test and post-test, then analyzed using the Paired Samples T-Test. The results of the analysis showed a significant improvement in a healthy lifestyle after the implementation of sports activities, with a mean difference of -2.200 (SD = 0.941) and a t(14) = -9.054 significance p = 0.000 (p < 0.05). These findings indicate that regular exercise activities can improve the quality of life of mothers in physical, mental, and social aspects, and support the implementation of a healthy lifestyle.